KARAKTERISTIK WARNA DAN AKTIVITAS ANTIOKSIDAN ANTOSIANIN UBI JALAR UNGU [Color Characteristics and Antioxidant Activity of Anthocyanin Extract from Purple Sweet Potato] - Ai Mahmudatussa’adah; Dedi Fardiaz; Nuri Andarwulan; Feri Kusnandar (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2014)
Anthocyanin is a natural pigment with color varying from red, purple, blue to yellow. The stability of its anthocyanin color is affected by pH, temperature and light. Purple sweet potato is rich in anthocyanin, particularly a stable acylated anthocyanin. This research was conducted to study the effect of pH on color and antioxidative activity of anthocyanin extracted from purple sweet potatoes harvested from Cilembu-Sumedang, Banjaran-Bandung, and Pakembangan-Kuningan. The experiments applied a completely randomized design with two replicates analyzed triplo.The results showed that the total number of monomeric anthocyanin in purple sweet potato harvested from Cilembu (3.78±0.08 mg cyanidin-3-glucoside/g dry weight, dw) was higher than that of Banjaran (3.18±0.01 mg/g) and Pakembangan (2.25±0.01 mg/g). The color of purple sweet potato anthocyanin extract was pH dependent. The color changed from red, faded red, purple, blue, green and yellow along with the increase of pH from 1 to 14. The content of anthocyanins from three locations of purple sweet potatoes differed from each other (p<0.05). Radical scavenging activity and reducing power of purple sweet potato anthocyanins extract at pH 1 was higher than that at pH 4.5 and pH 7.